Perioperative blood pressure alterations after eversion and conventional carotid endarterectomy sustain in the midterm - Demirel, Serdar; Attigah, Nicolas; Bruijnen, Hans; Hakimi, Maani; Burgmer, Benedikta; Böckler, Dittmar (Langenbeck's archives of surgery, 2013)
Carotid endarterectomy (CEA) is associated with a profound effect on blood pressure. The aim of this study was to evaluate 24 h ambulatory blood pressure measurement (ABPM) after eversion (E-CEA) and conventional (C-CEA) endarterectomy including a midterm follow-up.
Gesehen am 11.12.2020